Varicocele – impact on fertility and results of various methods of surgical treatment - Szymańska, Ewa; Ostaszewska, Sandra; Świąder, Kinga; Augustynowicz, Kinga; Chrzanowski, Jakub (Journal of Education, Health and Sport, 2023)
Introduction: Varicoceles, a dilation of veins within the pampiniform plexus, are present in ∼15% of the general male population. In this article we reviewed the epidemiology, symptoms, and various surgical techniques for the treatment of varicoceles and the results of following treatment. Material and methods: The work was based on medical articles collected in PubMed, websites and medical books. The research was conducted by looking at keywords such as: "Varicoceles", "varicocelectomy" and “infertility”. Results: There are many methods of treating varicoceles ranging from Microsurgical subinguinal varicocelectomy (MSV) or Laparoscopic varicocelectomy. Conclusions: The interdisciplinary approach to the patient and innovative surgical techniques can provide us with many solutions in the treatment of the disease. Doctors should adjust treatment to provide the best therapeutic effects.